The Formulation of Islamic Accounting Views In Syekh Siti Jenar Nusantara Sufism - Arwani, Agus (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2020)
This study aims to analyze islamic accounting evolved through two approaches believed to exist items, namely theoretical philosophical and pragmatic / practical schools. Especially for theoretical philosophical flow there is a unique perspective in the effort to design the character of the financial statements of Islamic accounting in the view of Siti jenar in the framework of Nusantara Sufism . This article is a focus literature method, although initially rarely noticed in qualitative research methodologies. .It is Necessary aspects of ethics in the accounting value Refers to the philosophy of manunggaling kawulo gusti meaningful value based accounting in Islamic studies and the Lord be the ultimate goal and Become the ultimate goal of human life. With Siti jenar concept based manunggaling kawulo gusti, then accounting capitalists will not exist, otherwise the concept of accounting profit According to the teachings of Islam would be more readily accepted by the Muslim community.Accounting growing niche to be dominated by the capitalists, this accounting value is no longer free. As modern accounting concepts currently very thick with the feel EGOMAU (egoistic, materialistic, and utility) that emphasizes consideration and achievement of the company's profit figures that can not be denied again, capitalist accounting help Prevent the crisis.